Research Review of the Books written by the Scholars of District Haripur in Islamic Studies - Muhammad Ikramullah; Muhammad Umar (Journal of Islamic and Religious Studies, 2018)
In this article, twelve scholars of District Haripur have been discussed for their significant contribution in Islamic sciences and various religious issues. The fact remains that District Haripur has remained the center for Islamic education wherein almost every school of thought has existed. In this article, those scholars are provided expression who despite been a part of some particular school of thought, have always encouraged intra-faith harmony. For example, "Al Ribat li Rad Hiyla al Isqat" by Maulana Mohammad Azam contains plenty of updated information on this issue. Similarly, another book called as "Mu'in-ul-'Aqaid” by Maulana Mohammad Hassan, provides grounds for rejecting the hypocrisy of society in a befitting manner. Before writing this article, a session was held with those scholars who are still alive whereas details of those dead were collected from their family members.